Maritime-related cults in the coastal cities of Philistia during the Roman period: legacy and change - Rodan, Simona (Archaeopress Roman archaeology ;, 2019)
Maritime-Related Cults in the Coastal Cities of Philistia during the Roman Periodquestions the origins and the traditions of the cultic rites practised during Roman times along the southern shores of the Land of Israel. This area was known since biblical times as 'Peleshet' (Philistia), after the name of one of the Sea Peoples that had settled there at the beginning of the Iron Age. Philistia's important cities Jaffa, Ashkelon, Gaza and Rafiah were culturally and religiously integrated into the Graeco-Roman world. At the same time, each city developed its own original and unique group of myths and cults that had their roots in earlier periods. Their emergence and formation were influenced by environmental conditions as well as by ethno-social structures and political circumstances. Philistia's port cities served as crossroads for the routes connecting the main centres of culture and commerce in ancient times. Most of their cults were closely associated with the sea, and reflect the existential dependency of the inhabitants on the sea that supplied them with sustenance and livelihood and was regarded as a divine beneficent power. The myths also echo the lives of the sailors, their beliefs and fears derived from encountering the dangers of the sea: storms, floods, reefs and giant fish portrayed as monsters. The population of the cities was of mixed and varied ethnic and cultural origins. This was the result of the waves of conquests and migrations over the ages, yet each city was noted for its unique ethnic components. The book also deals with the political circumstances, which had a decisive impact on the formation of religious life and cultic rites in all four cities. It sheds new light to the understanding of the events and historical processes in the region